FINANCIAL SATISFACTION ON MILLENNIALS: EXAMINING THE RELATIONSHIP BETWEEN FINANCIAL KNOWLEDGE, DIGITAL FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, AND FINANCIAL BEHAVIOR - Normawati, Rani Arifah; Rahayu, Sri Mangesti; Worokinasih, Saparila (Jurnal Aplikasi Manajemen, 2022)
It is essential to know the financial satisfaction of the millennials because they are prone to experiencing financial problems due to their characteristics and the complexity of Digital Financial Services (DFS). Millennials are responsible for their financial decisions to increase financial satisfaction, so the meaning of financial attitudes, and financial knowledge, coupled with digital financial knowledge, is significant for financial decisions and behavior. This study examines the factors that predict financial satisfaction and examine the mediated effect of financial behavior on the relationship between financial knowledge, digital financial knowledge, financial attitude, and financial satisfaction. A sample of 306 millennials on Surabaya was selected. A quantitative analysis technique using PLS was applied. The final model showed financial knowledge, digital financial knowledge, and financial attitudes positively influence financial behavior. Financial behavior significantly moderates the relationship between financial knowledge, digital financial knowledge, financial attitude, and financial satisfaction.